Espacio, integración y desarrollo : La integración concertada del espacio económico - Boudeville, Jacques R. (1967)
Concerned about the disintegration of spaces and humanity, the author asks: "What exactly are integration and the economic space of man?". In answering this question, he resorts to three concepts of space: the geographical, the mathematical, and the economic one, and, with Perroux, believes that the latter can be approached from three different angles, which will indicate the three meaning and scopes of the word integration. Thus, an economy is not to be considered as integrated when insufficiently homogeneous (as is the case with the north and south of Italy); when it is insufficiently polarized, i.e. when the economic interdependencies are insufficient (as is the case with EFTA); when it does not have a well-defined economic target, nor has at its disposal instruments of economic and financial policy (as is the case with the Common Market). For reasons of simplification the author in essence studies integration from the viewpoint of polarized space, distinguishing vertical integration or functional polarization, from horizontal integration and regional polarization. He ends up with reflections on concert integration, which latter he considers as an element of progress.